The interrelationships between social networking site use, school connectedness, peer connectedness and social competence, and their influence on early adolescent wellbeing: an exploratory study - Girdham, Sharon (2017)
Concerns for early adolescent mental health have increased, leading to consideration of how to optimise the psychological wellbeing of children and young people within secondary school contexts (HM Government, 2017). Parallel to this is growing recognition that online social networking sites (SNS) occupy a pivotal role in how early adolescents communicate and interact with each other (Olufadi, 2016). Understanding the implications of SNS use, and harnessing any potential to enhance wellbeing has been identified as a relevant aspect of future strategies aiming to support early adolescent development and social functioning (DoH, 2015).